If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 4 + -2x Solving 12 = 4 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 12 + 2x = 4 + -2x + 2x Combine like terms: -2x + 2x = 0 12 + 2x = 4 + 0 12 + 2x = 4 Add '-12' to each side of the equation. 12 + -12 + 2x = 4 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = 4 + -12 2x = 4 + -12 Combine like terms: 4 + -12 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 6=-3x(x+4) | | 5=7-2x | | (x+10)+x+(x+5)=180 | | 5(x-4)=5x+12 | | -22=-10+b | | -1(-3)(-6)= | | 9y^2+2=9y | | 14+3n=2 | | -168=-12a | | 7t-5=3t+11 | | 2v^2+3v=4 | | .25*x-6=.75*x+14 | | 11=5+x | | 5x^3-10x^2+40x=0 | | 32=-16p | | -34=v+42-5p | | 6x+47+12=257 | | 5w+2=2w+2 | | 69y=3y | | 0=x^2-10x-10 | | 19=y-7 | | y+(y-30)+90=180 | | -8=4x+24+8x | | 23-7(x)=117 | | m+2m+(y-30)=180 | | -3(x-4)+5=2x-2 | | 3(x+6)=2(x-3) | | 180-(2x-20)=2x | | 5x+30=9x-10 | | -27-8a=5(-3a+7)-6 | | (-x)(3x^2+x-1)= | | 1.5c+4=.5c+13 |